Controllable synthesis of MoS2@MoO2 nanonetworks for enhanced NO2 room temperature sensing in air. Issue 17 (16th April 2019) - Ikram, Muhammad; Liu, Lujia; Liu, Yang; Ullah, Mohib; Ma, Laifeng; Bakhtiar, Syed ul Hasnain; Wu, Hongyuan; Yu, Haitao; Wang, Ruihong; Shi, Keying
Abstract : MoS2 @MoO2 with controllable morphology fabricated via a one-step CVD method showed enhanced NO2 sensing performance at room temperature in air. Abstract : MoS2 nanosheets (NSs) are a promising gas sensing material at room temperature (RT) due to their unique properties and structures. Unfortunately, the activity of pure MoS2 NSs is highly affected by the adsorption of atmospheric oxygen, which strongly influences the stability of MoS2 sensing devices and significantly hinders the practical applications of these sensors in air. Heterostructure formation may be an effective approach to modulate the intrinsic electronic properties of MoS2 NSs. In this study, thin MoO2 nanoplates (NPs) were decorated with multilayer MoS2 NSs via one-step controllable sulfurization to fabricate MoS2 @MoO2 nanonetworks, and remarkable gas sensing performance was achieved with high stability in air at RT. In particular, the MSO-2 (1 h sulfurization of the MoO2 NPs) nanonetworks with n–p heterojunctions demonstrated a high response of 19.4 to 100 ppm NO2 in a short period of time (1.06 s) with rapid recovery (22.9 s) to the baseline. The excellent gas sensing performance of the MSO-2 sensor is attributed to the synergistic effect of the MoS2 NSs and thin MoO2 NPs, which created heterojunctions/defects to easily transfer electrons and provide more active sites for NO2 gas. This simple synthetic method to design and fabricate n–p heterojunction sensors will be effective in commercial gas sensing applications.